Clinical significance and regulatory mechanism of miR-134-5p in rheumatic heart disease - Liangqin Yang; Juan Li; Ju Wang; Yaping Zhang; Yunyun Huang (BMC Cardiovascular Disorders)
Abstract Background Rheumatic heart disease (RHD) causes irreversible valvular injury and mortality globally. Easily detectable miRNAs may provide valuable perspectives into the clinical management of RHD. This study aimed to explore the role of miR-134-5p in RHD progression. Methods A total of 167 subjects (80 non-RHD, 87 RHD) were included in this study. The level of miR-134-5p was evaluated by qRT-PCR, and its diagnostic value was assessed by the receiver operator characteristic (ROC) curve. The correlation between miR-134-5p and RHD severity was evaluated by correlation analysis. The association between miR-134-5p expression and RHD prognosis was analyzed by the Kaplan-Meier survival analysis and multivariate COX regression analysis. The regulatory relationship between miR-134-5p and lysine acetyltransferase 7 (KAT7) was assessed by the dual-luciferase reporter assay. In vitro cell experiment was used to assess the regulatory mechanism of miR-134-5p in lipopolysaccharide (LPS)-induced human valvular interstitial cells (hVICs). Results Upregulated miR-134-5p in RHD was correlated with RHD severity and could diagnose RHD from rheumatic fever (RF). Low miR-134-5p level was associated with a better prognosis of RHD and could serve as an independent prognostic factor for RHD. Suppression of miR-134-5p in hVICs injury could attenuate the inflammation and oxidative stress by regulating the KAT7 expression. Conclusions Upregulated miR-134-5p expression showed a diagnostic and prognostic value in RHD. MiR-134-5p may be involved in RHD by regulating the inflammation and oxidative stress in hVIC injury via targeting KAT7.